CHOOSING OF SOME BLOOD PARAMETERS AND HEPATIC ENZYMES AS INDICATORS FOR RADIATION EXPOSURE IN EXPERIMENTAL RABBITS - Hanaa Salman Kadhim (Basrah Journal of Veterinary Research)
Injection of l mg / kg of uranyle acetate caused an obvious changes in the numbers of white blood cells with progressing time ofexperiment, specially in the numbers of neutropiiiles and monocytes which decreased significantly, while the numbers of eosinophiles has increased significantly after the first week of injection and then decreased significantly in the 2nd and 3rd week of exposure as compared with control group. Also, the injection caused significant decreasing in Hb and PCV values, while the activities of hepatic enzymes GPT, and GOT were not affected in comparison with control group. . So, it may be useful to use this variation of WBC percentage as a primary indication to persons who D exposed to different doses of radioactive compound